Ritual Puhora’ano Sangia pada Masyarakat Cia-Cia Burangasi Kabupaten Buton - La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT This research studies about puhora'ano sangia ritual as one of the local culture products of Cia-Cia Burangasi society, Buton regency, Southeast Sulawesi. Specifically, this study attempts to analyze how the ritual functions for the supporters of the present. The data in this study are obtained through participant observation and in-depth interviews then analyzed by descriptive qualitative. The result of the research shows that the puhora'ano sangia ritual in existence has some function in supporting the community, that are religious, social, cultural inheritance, work ethics and environmental wisdom. In religion, puhora'ano sangia ritual is a means to establish communication with the supernatural power to be given the protection of the various demons that threaten their agricultural activities. Socially, puhora'ano sangia ritual is a means of social control, social media and social norms, and grouping (social alignment). As a cultural inheritance, judging from the number of children involved in the ritual procession by itself can capture the values that exist in them, instilled in him and ultimately sought to preserve the culture. The function of work ethic, it can be seen from the effort and hopes to obtain better results than the previous harvest. While from the point of environmental wisdom, this ritual is as a means to re-live the inaugural worldview those who see supernatural beings, man and nature as an integral unity and interdependence, so that when damage the natural is a means of self-destructive. Key words: function, puhora'ano sangia ritual